Relation of dental age to chronological age among Filipinos at mixed dentition stage - Jacob, Jr., Romeo N. (The Journal of the Philippine Dental Association)
The purpose of this study was to determine the correlation of the Filipino patients dental age with its chronological age whether there is a significant delay or advance in the dental age utilizing the Haslund dental age scoring. It also aimed to determine if difference in proportion exists in the maxilla and mandible for both male and female, the proportion of normal against delayed, the existing relationship between dental age and sex, and the mean year delay for both male and female in relation to maxilla and mandible.